2015
DOI: 10.1371/journal.pone.0130945
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone Involvement in the Ustilago maydis– Zea mays Pathosystem: Relationships between Abscisic Acid and Cytokinin Levels and Strain Virulence in Infected Cob Tissue

Abstract: Ustilago maydis is the causative agent of common smut of corn. Early studies noted its ability to synthesize phytohormones and, more recently these growth promoting substances were confirmed as cytokinins (CKs). Cytokinins comprise a group of phytohormones commonly associated with actively dividing tissues. Lab analyses identified variation in virulence between U. maydis dikaryon and solopathogen infections of corn cob tissue. Samples from infected cob tissue were taken at sequential time points post infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 70 publications
4
62
0
2
Order By: Relevance
“…On the other hand, no active FB fraction and no cZ form CKs 245 were detected in cedar control twigs. In a similar manner, infected apple tissue comprised of 246 pycnia on the upper (adaxial) and aecia on the lower (abaxial) leaf surface where the aeciospore 247 production occurs, had much different hormone profiles than the non-infected control leaves.D r a f t development suggests that the fungus is excreting hormones using the common or modified 250 mevalonate (MVA) pathway, similar to the one described for U. maydis, a fungus infecting corn 251 (Morrison et al 2015a(Morrison et al , 2017 and consistent with the signature CK pathway reported from a 252 large survey of fungal species (Morrison et al 2015b). On the contrary, in the non-infected 253 control cedar twigs and apple leaves the plant methylerythritol phosphate (MEP) pathway was 254…”
Section: Discussion 232supporting
confidence: 53%
“…On the other hand, no active FB fraction and no cZ form CKs 245 were detected in cedar control twigs. In a similar manner, infected apple tissue comprised of 246 pycnia on the upper (adaxial) and aecia on the lower (abaxial) leaf surface where the aeciospore 247 production occurs, had much different hormone profiles than the non-infected control leaves.D r a f t development suggests that the fungus is excreting hormones using the common or modified 250 mevalonate (MVA) pathway, similar to the one described for U. maydis, a fungus infecting corn 251 (Morrison et al 2015a(Morrison et al , 2017 and consistent with the signature CK pathway reported from a 252 large survey of fungal species (Morrison et al 2015b). On the contrary, in the non-infected 253 control cedar twigs and apple leaves the plant methylerythritol phosphate (MEP) pathway was 254…”
Section: Discussion 232supporting
confidence: 53%
“…Since ABA is often reported to play a role in attenuating defence reactions towards biotic stress (Cao et al , ; Clay et al , ; Mialoundama et al , ), attempts to elevate ABA levels might be a genuine strategy for pathogens to manipulate their hosts. This can occur by producing ABA themselves (Cao et al , ; Morrison et al , ; Siewers et al , ; Spence et al , ; de Torres‐Zabala et al ., ) or by activation of the plant ABA biosynthesis, for example via enhancing NCED3 gene expression as observed in the X. oryzae –rice interaction, resulting in increased susceptibility (Xu et al , ). Similar observations have been made for Pseudomonas syringae DC3000, which deploys type III effectors to induce the Arabidopsis NCED3 gene, resulting in elevation of ABA levels (de Torres‐Zabala et al , , ).…”
Section: Discussionmentioning
confidence: 99%
“…Some bacterial pathogens are even able to manipulate the phytohormone homeostasis by increasing ABA levels in plants, thereby compromising plant defence reactions (de Torres‐Zabala et al , , ). As demonstrated in the Ustilago maydis – Zea mays pathosystem, the fungus was capable of producing ABA, resulting in increased ABA levels within the plant cells at the early infection stages, which probably serves as part of the fungal virulence strategy (Morrison et al , ). Similar observations have been reported by works on B. cinerea, Cercospora spp., Fusarium spp., Rhizoctonia spp., Magnaporthe grisea and Magnaporthe oryzae (Cao et al , ; Siewers et al , ; Spence et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, CKs are associated with virulence of U. maydis infection on maize (Morrison et al, 2015). In L. maculans , the decrease in LmIPT observed in our study did not considerably affect its virulence (Supplementary Figure 4C).…”
Section: Discussionmentioning
confidence: 99%